2020
DOI: 10.1371/journal.pone.0230677
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic journey in Spinal Muscular Atrophy: Is it still an odyssey?

Abstract: Background The advent of new therapies has increased the need to achieve early diagnosis in Spinal Muscular Atrophy (SMA). The aim of the present study was to define the age of diagnosis in the three main types of SMA with pediatric-onset and the timing between the recognition of clinical signs and confirmed genetic diagnosis. Methods All patients with a confirmed diagnosis of type I, II, III SMA followed in 5 Italian centers were included in this study, assessing age at symptoms onset, presenting sign or symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 30 publications
1
46
0
2
Order By: Relevance
“…This is a consequence of the rapid denervation process occurring in the first six months of life and the aim of pre-symptomatic treatment is the precocious rescue of motoneurons. However, we recently demonstrated that the mean age at diagnosis is 4.70 months (SD ± 2.82) in SMA type I, 15.6 months (SD ± 5.88) in SMA type II, and 4.34 years (SD ± 4.01) in SMA type III [ 73 ]. Therefore, these findings support the need of NBS to achieve a better efficacy of the available therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…This is a consequence of the rapid denervation process occurring in the first six months of life and the aim of pre-symptomatic treatment is the precocious rescue of motoneurons. However, we recently demonstrated that the mean age at diagnosis is 4.70 months (SD ± 2.82) in SMA type I, 15.6 months (SD ± 5.88) in SMA type II, and 4.34 years (SD ± 4.01) in SMA type III [ 73 ]. Therefore, these findings support the need of NBS to achieve a better efficacy of the available therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…2 The clinical subtypes, based on age of onset and maximum motor function achieved, range from the most severe SMA type I to the mildest SMA type IV. 3 SMA has a cumulative incidence of 1 in 11,000 live births. 4 However, the epidemiologic burden of SMA is not equally divided over the subtypes.…”
mentioning
confidence: 99%
“…The disease is caused by mutations in the survival motor neuron 1 ( SMN1 ) gene 2 . The clinical subtypes, based on age of onset and maximum motor function achieved, range from the most severe SMA type I to the mildest SMA type IV 3 …”
mentioning
confidence: 99%
“…Notably, there were manifestations of reduced muscle strength in the legs or CMAPs < 1 mV (N. ulnaris), which at this time would have been missed on a routine examination. NBS avoided a diagnostic delay which otherwise still is the rule 25,26 . Since SMN expression is highest prenatally 5 , it is reasonable that motor neuron death already occurs to some extent before birth.…”
Section: Discussionmentioning
confidence: 99%